Stability estimate for the broken non-abelian x-ray transform in Minkowski space. (1st October 2022) - St-Amant, Simon
Abstract: We study the broken non-abelian x-ray transform in Minkowski space. This transform acts on the space of Hermitian connections on a causal diamond and is known to be injective up to an infinite-dimensional gauge. We show a stability estimate that takes the gauge into account, leading to a new proof of the transform's injectivity. Our proof leads us to consider a special type of connections that we call light-sink connections. We then show that we can consistently recover a light-sink connection from noisy measurement of its x-ray transform data through Bayesian inversion.